2019
DOI: 10.1055/s-0039-1698832
|View full text |Cite
|
Sign up to set email alerts
|

Subfoveal Choroidal Thickness and Associated Changes of Angiogenic Factors in Women with Severe Preeclampsia

Abstract: Objective Severe preeclampsia complicates roughly 1% of all pregnancies. One defining feature of severe preeclampsia is new onset visual disturbance. The accessibility of the choroid to high-resolution, noninvasive imaging makes it a reasonable target of investigation for disease prediction, stratification, or monitoring in preeclampsia. This study aimed to compare subfoveal choroidal thickness between women with severe preeclampsia and those with normotensive pregnancies, and to investigate associations betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…It was demonstrated that the choroid was responsive to circulating angiogenic factors, such as soluble endoglin (sEng), placental growth factor (PlGF) and VEGF [ 23 , 24 ]. Stern-Ascher et al [ 8 ] found a positive association of PlGF with central CT in severe pre-eclampsia, suggesting that intravascular inflammation and vasoconstriction caused by pre-eclampsia does affect CT. In the study comparing CT among three groups of normotensive non-gravid, normotensive postpartum and pre-eclampsia postpartum women using EDI OCT, Garg et al [ 9 ] reported that pre-eclampsia postpartum cases had greater CT and retinal macular volume than normotensive postpartum without difference of these values between normotensive postpartum and normotensive non-gravid women and suggested that it was due to higher serum-VEGF concentration in pre-eclampsia patients than normotensive pregnant women, which was reported by Celik at al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was demonstrated that the choroid was responsive to circulating angiogenic factors, such as soluble endoglin (sEng), placental growth factor (PlGF) and VEGF [ 23 , 24 ]. Stern-Ascher et al [ 8 ] found a positive association of PlGF with central CT in severe pre-eclampsia, suggesting that intravascular inflammation and vasoconstriction caused by pre-eclampsia does affect CT. In the study comparing CT among three groups of normotensive non-gravid, normotensive postpartum and pre-eclampsia postpartum women using EDI OCT, Garg et al [ 9 ] reported that pre-eclampsia postpartum cases had greater CT and retinal macular volume than normotensive postpartum without difference of these values between normotensive postpartum and normotensive non-gravid women and suggested that it was due to higher serum-VEGF concentration in pre-eclampsia patients than normotensive pregnant women, which was reported by Celik at al.…”
Section: Discussionmentioning
confidence: 99%
“…High vascular density (VD) and fenestrated capillaries of the choroid make it sensitive to systemic changes. An imbalance of circulating anti-angiogenic factors including soluble fms-like tyrosine kinase 1 (sFLT1) and angiogenic factors such as vascular endothelial growth factor (VEGF) plays a role in endothelial dysfunction in patients with pre-eclampsia, which in turn influences ocular environment, especially choroid [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 This is supported by our prior OCT observation of increased retinal and choroidal thickness in certain subsets of PE. 31 , 32 We hypothesized that that this subclinical edema might originate from changes in the Vascular Endothelial Growth Factor (VEGF)-sensitive choriocapillaris. 33 In the present study, we observed reduced resistance in the choroid.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, OCT angiography (OCT-A) can provide detailed imaging of the vascular structures of the retina and choroid repeatedly and noninvasively. Using this OCT technology, researchers have studied the correlation between maternal serologic changes in preeclampsia and ocular characteristics [ 16 , 17 ]. However, to our knowledge, no research on the relationship between the sFlt-1/PlGF ratio and ocular structural changes has been reported to date.…”
Section: Introductionmentioning
confidence: 99%